A patient with vertebral, cognitive and behavioural abnormalities and a de novo deletion of NRXN1α. Issue 4 (5th December 2007) - Zahir, F R; Baross, A; Delaney, A D; Eydoux, P; Fernandes, N D; Pugh, T; Marra, M A; Friedman, J M
Abstract : The authors report a patient with mild mental retardation, autistic features, multiple vertebral malformations, and an unusual facial appearance who carries a de novo submicroscopic deletion of chromosome 2p16.3. The patient's deletion is ∼320 kb in size and includes only the part of the NRXN1 gene that codes for the neurexin1α promoter and initial coding exons. The more downstream neurexin1β promoter and the region surrounding it are intact. Neurexin1β has been associated with autism in several recent studies, but this is the first reported patient with loss of only neurexin1α and not of neurexin1β. These findings suggest that neurexin1α function in correct dosage is necessary for normal neurological development.